A STUDY OF THINKING STYLES OF PROSPECTIVE TEACHERS IN RELATION TOTHEIR STREAM” - Dixit, Ravindra Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
The Present Study assesed the Thinking styles of prospective Teachers in relation to their streams. The sample consisted 371 Prospective teachers (Male = 198, Female = 173) who were selected from B.Ed. colleges of Dr. B.R.A University Agra by using accidental technique of sample selection. In the Present study the Normative survey method of Research was used. Thinking style Inventory (T.S.I.) constructed by Sternberg &Wagner was employed for data collection. Prospective teachers belonging to science, arts and Commerce stream differed significantly in few styles of thinking. Science prospective teachers were more legislative, more local and more external than prospective teachers belonging to arts and commerce stream. On rest of thinking styles viz, integrated, executive, judicial, monarchic, hierarchic, oligarchic, anarchic, global, internal, liberal and conservative, no significant difference were found among Prospective Teachers of science, arts and Commerce Streams.